2015
DOI: 10.1089/jir.2014.0038
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine-Inhibited Dengue Virus Is Associated with Host Defense Machinery

Abstract: Hydroxychloroquine (HCQ) is an antimalarial drug also used in treating autoimmune diseases. Its antiviral activity was demonstrated in restricting HIV infection in vitro; however, the clinical implications remain controversial. Infection with dengue virus (DENV) is a global public health problem, and we lack an antiviral drug for DENV. Here, we evaluated the anti-DENV potential of treatment with HCQ. Immunofluorescence assays demonstrated that HCQ could inhibit DENV serotype 1-4 infection in vitro. RT-qPCR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 67 publications
2
92
1
3
Order By: Relevance
“…Cells cultured in 12-well plates were transfected with NF-κB-Luc reporter plasmids (46) by TurboFect. pRL-TK (Promega), encoding Renilla luciferase under a herpes simplex virus thymidine kinase promoter, was an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Cells cultured in 12-well plates were transfected with NF-κB-Luc reporter plasmids (46) by TurboFect. pRL-TK (Promega), encoding Renilla luciferase under a herpes simplex virus thymidine kinase promoter, was an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that CQ/HCQ possess a broad spectrum of antiv iral effects on a variety of viruses as diverse as human immunodeficiency virus (HIV) [30], Marburg virus, Zika virus [31], dengue virus [32], Ebola virus [33], and SARS-Co V-1 [34,35], etc. CQ and HCQ can interfere with the binding of viral particles to their cellular cell surface receptor or the pH-dependent endosome-med iated viral entry of enveloped viruses to inhibit the v iral cycle [32]. They can also interfere with the post-translational modification of viral proteins or impair the proper maturation of viral p rotein by pH modulation [36].…”
Section: Jak Inhibitorsmentioning
confidence: 99%
“…Several antimalarial drugs that contain a quinoline scaffold were evaluated for their antiviral activity against DENV [260][261][262] or WNV 260 . Amodiaquine inhibited DENV-2, DENV-4 and WNV replication but with relatively poor selectivity 260 .…”
Section: Polyamine Synthesis Inhibitorsmentioning
confidence: 99%